2015
DOI: 10.1177/0268355515592076
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine is associated with the severity of primary chronic venous disease

Abstract: Serum homocysteine is positively associated with the severity of primary chronic venous disease and therefore could play a role in promoting chronic venous disease complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…19 Several studies have revealed a positive correlation between serum Hcy and the severity of primary CVDs. 20,21 Our study also identified HHcy as a significant risk factor for the development of venous ulceration. In the study population, a high BMI seemed to have no effect on developing ulcers.…”
Section: Discussionsupporting
confidence: 62%
“…19 Several studies have revealed a positive correlation between serum Hcy and the severity of primary CVDs. 20,21 Our study also identified HHcy as a significant risk factor for the development of venous ulceration. In the study population, a high BMI seemed to have no effect on developing ulcers.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, a meta-analysis encompassing 36 studies and involving 60,754 subjects from 19 provinces and municipalities in China found that the prevalence of HHcy was notably higher in men than in women ( 21 ). Furthermore, elevated levels of serum homocysteine have been observed in male patients with hypertension ( 23 ), primary chronic venous disease ( 24 ), and psoriasis ( 25 ). Potential factors contributing to the observed sex-specific variation encompass disparities in muscle mass, estrogen levels, lifestyles, and vitamin levels.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of healthy people demonstrated that serum homocysteine levels are higher in males than in females [ 19 ]. Elevated serum homocysteine levels have been reported in male patients with hypertension, cardiovascular disease, primary chronic venous disease, and glaucomatous disease [ 20 , 21 , 22 , 23 ]. Previous studies also indicate that further factors, such as a surge in blood lead and cadmium levels, could increase homocysteine levels in males [ 24 ].…”
Section: Discussionmentioning
confidence: 99%